Implementasi Pendaftaran Hak Tanggungan secara Elektronik - Djakatara, Vanny; Paserangi, Hasbir; Nur, Sri Susyanti (Faculty of Law, Institut Ilmu Sosial dan Bisnis Andi Sapada., 2023)
Guarantee law is very important in sustaining development and economic recovery which is being actively implemented in Indonesia. The land guarantee institution is one of the guarantees that has the ability to provide legal certainty in protecting the guarantor and the guarantee recipient, or commonly called the mortgage right. This study aims to analyze the implementation of electronic mortgage registration in Gorontalo District. This research is an empirical legal research that uses primary legal data and secondary legal sources. The data obtained, both primary data and secondary data, were then analyzed qualitatively. The results of the study show that the implementation of electronic mortgage registration has several obstacles in the socialization process. There are still many people who have not received information regarding the process and implementation of registration of mortgage rights electronically. In carrying out online registration, officers also face obstacles, for example in terms of inadequate network availability devices. ___ Referensi Buku dengan penulis: Harsono, Boedi. (1999). Hukum Agraria Indonesia, Sejarah Pembentukan UUPA, Isi dan Pelaksanaannya. Jakarta: Djambatan. Rahman, H. (1995). Aspek-Aspek Hukum Pemberian Kredit Perbankan di Indonesia. Bandung: Citra Aditya Bakti. Santoso, Urip. (2019). Pendaftaran dan Peralihan Hak Atas Tanah. Jakarta: Kencana. Sjahputra, Iman. (2002). Problematika Hukum Internet Indonesia. Jakarta: PT Prenhallindo. Sutedi, Adrian. (2006). Implikasi Hak Tanggungan terhadap Pemberian Kredit oleh Bank dan Penyelesaian Kredit Bermasalah. Jakarta: BP Cipta Jaya. Artikel jurnal: Ahmad, G. A. (2018). Masterplan Percepatan dan Perluasan Pembangunan Ekonomi Indonesia (MP3EI), Sengketa Agraria dan Viktimologi: Studi Kasus Pembangunan New Yogyakarta International Airport (NYIA). Jurnal Ilmiah Galuh Justisi, 6(1), 12-24. Alimuddin, N. H. (2021). Implementasi Sertifikat Elektronik sebagai Jaminan Kepastian Hukum Kepemilikan Hak Atas Tanah di Indonesia. SASI, 27(3), 335-345. Andriyani, K., & Surata, I. G. (2016). Pendaftaran Tanah Secara Rechts Kadaster Melalui Proses Konversi (Studi Kasus Di Kantor Pertanahan Kabupaten Buleleng). Kertha Widya, 4(2), 89-112. Azizah, N., Barkatullah, A. H., & Hafidah, N. (2022). Pendaftaran Hak Tanggungan Secara Elektronik (Studi di Kantor PPAT Wilayah Banjarmasin Utara). Notary Law Journal, 1(2), 84-99. Dewi, I. G. S., & Ardani, M. N. (2020). Kebijakan Penjaminan Tanah melalui Hak Tanggungan di Indonesia (Studi Penjaminan Hak Tanggungan Elektronik di Kabupaten Badung Provinsi Bali). Law, Development and Justice Review, 3(1), 57-69. Hutagalung, A. (2008). Praktek Pembebanan dan Pelaksanaan Eksekusi Hak Tanggungan di Indonesia. Jurnal Hukum & Pembangunan, 38(2), 148-174. Imanda, N. (2020). Lahirnya Hak Tanggungan menurut Peraturan Pemerintah Agraria tentang Pelayanan Hak Tanggungan Terintegrasi secara Elektronik. Jurnal Notarie, 3(1), 151-164. Koswara, I. Y. (2016). Pendaftaran Tanah Sebagai Wujud Kepastian Hukum Dalam Rangka Menghadapi Masyarakat Ekonomi Asean (MEA). Jurnal Hukum Positum, 1(1), 23-38. Mooduto, M. F., Wulansari, H., & Riyadi, R. (2021). Pengelolaan Warkah Digital dan Integrasinya dengan Data Spasial Bidang Tanah Menuju Pelayanan Online di Kabupaten Bantul. Tunas Agraria, 4(2), 250-274. Nurwulan, P. (2021). Implementasi Pelayanan Hak Tanggungan Elektronik bagi Kreditor dan Pejabat Pembuat Akta Tanah. Jurnal Hukum Ius Quia Iustum, 28(1), 183-202. Sagari, D., & Mujiati, M. (2022). Efektivitas Layanan Hak Tanggungan Terintegrasi secara Elektronik di Kantor Pertanahan Kabupaten Klaten. Tunas Agraria, 5(1), 33-46. Supryadi, W. (2022). Analisis Terhadap Inovasi Pengikatan Hak Tanggungan (HT) Berbasis Elektronik di Wilayah Kerja Kantor Badan Pertanahan Dompu. Journal of Innovation Research and Knowledge, 1(9), 965-980. Usanti, T. P. (2012). Lahirnya Hak Kebendaan. Perspektif, 17(1), 44-53. Yusuf, W. O. F., Sumardi, J., & Paserangi, H. (2015). Peran Notaris Dalam Proses Penerbitan Sertifikat Elektronik Berdasarkan Undang-Undang Informasi dan Transaksi Elektronik. Jurnal Universitas Hasanuddin, 4(1). 67-73.